Analisis Kapasitas Persimpangan Pada Daerah Kabupaten Tanah Laut (Studi Kasus Bundaran Simpang Tiga Angsau) - Hendra Putra; Muhammad Rizan Adam (Jurnal Teknologi Berkelanjutan, 2026)
The Angsau Three-Way Intersection, located in Pelaihari District, Tanah Laut Regency, South Kalimantan Province, serves as a key junction connecting several surrounding cities and regencies. Over time, the steady increase in population has contributed to a rise in transportation usage, leading to higher traffic volumes within Tanah Laut. Consequently, a study is required to assess the traffic service level at the Angsau Intersection to determine appropriate future improvements. Referring to the Pedoman Kapasitas Jalan Indonesia (PKJI) 2023 and utilizing the Indonesia Road Capacity Analysis software (KAJI), this research aims to provide comparative insights as well as recommendations for future development at the intersection. Based on the collected data and analysis, the highest traffic density occurs during weekends, with peak traffic volume recorded between 16:40–17:40 at 3,945 vehicles/hour. The resulting Level of Service indicates that the intersection is approaching the threshold of the Degree of Saturation (Dj), with a value of 0.76 (Dj < 0.80). The initial improvement effort to address the increasing traffic flow involves geometric enhancements on both the minor and major roads, along with the construction of a median of at least 3 meters, which effectively reduces the Dj value to 0.61 (Dj < 0.80). A second improvement alternative—geometric modifications on the minor and major roads—also proves effective in lowering the Dj value to 0.61 (Dj < 0.80).